Analysis of Factors Influencing Exclusive Breastfeeding Practices in Kramat Gajah Village, Deli Serdang - Emi Inayah Sari Siregar; Tinah Tinah; Abdul Hairuddin Angkat (Universitas Islam Negeri Sumatera Utara, Medan, 2025)
Exclusive breastfeeding (EBF) is the optimal method of feeding infants from birth to six months without providing any additional food or drink. Exclusive breastfeeding is influenced by maternal age, knowledge, education level, andemployment status, household income, and support from healthcare workers. This study aims to analyze the association among maternal age, knowledge, education, employment status, household income, and healthcare worker support with the practice of exclusive breastfeeding. A quantitative, descriptive study with a cross-sectional approach was implemented in Kramat Gajah Village. The study population consists of breastfeeding mothers with infants aged 0-6 months, selected through total sampling. Independent variables are maternal age, education level, household income, employment status, maternal knowledge, and healthcare worker support, while the dependent variable is exclusive breastfeeding. Data were gathered through a structured questionnaire, and statistical analysis was carried out using the Chi-square test. A total of 65 breastfeeding mothers participated in the study. The majority of respondents exclusively breastfed their infants (75.4%), were aged 20-35 years (78.46%), had an education level of junior or senior high school (84.62%), had a household income greater than or equal to the regional minimum wage (≥ IDR 3,255,572; 53.84%), were unemployed (83.1%), and received support from healthcare workers (84.6%). The Chi-square test results revealed significant associations between exclusive breastfeeding practices and maternal knowledge (p=0.003), education (p=0.049), and employment status (p=0.011). In contrast, no significant associations were found between exclusive breastfeeding and maternal age (p=0.118), household income (p=0.424), or healthcare worker support (p=0.220). Therefore, maternal knowledge, education level, and employment status significantly influence exclusive breastfeeding practices in Kramat Gajah Village, whereas maternal age, household income, and healthcare worker support do not show significant associations Keywords: Exclusive Breastfeeding, Determinants, Maternal Knowledge, Maternal Education, Breastfeeding Practices